Policy Implications of Incorporating E-Jeepney in Public Transport Systems: Lessons from Valenzuela City, Philippines - Dapigran, Jenise Deniel M.; Ghener, T. Garra; Francis, J. Medrano Mark (International Journal of Research in Interdisciplinary Studies, 2025)
This paper examines the feasibility of implementing E-jeepneys as an alternative mode of transportation in Valenzuela City, a leading city in the Philippines known for its sustainability, infrastructure development, and innovative programs. Jeepneys are the most commonly used mode of public transportation in the country, with around 1,500 registered traditional jeepneys in Valenzuela City providing a livelihood for approximately 1,000 families. However, the jeepney industry in Metro Manila is becoming increasingly competitive due to the introduction of cheaper and more modernized models. To address this issue, this study utilizes sustainable development as a conceptual framework to evaluate the economic and socio-political aspects of implementing e-jeepneys under the Public Utility Vehicle Modernization Program (PUVMP). The paper presents the findings of a survey conducted among jeepney driver-operators regarding their willingness to undergo jeepney modernization. The survey results revealed that a majority of respondents were open to the idea, citing economic benefits, improved vehicle performance, and government support as primary reasons. Moreover, the local government officials in Valenzuela City expressed support for the implementation of e-jeepneys, citing their potential to address issues such as air pollution, traffic congestion, and energy efficiency, among others. The paper concludes by recommending the adoption of e-jeepneys as an effective and sustainable alternative to traditional jeepneys in Valenzuela City. The study provides insights and recommendations that can guide policymakers and stakeholders in implementing sustainable transportation solutions in the Philippines. Overall, this study contributes to the body of scholarly literature on sustainable transportation and provides valuable insights into the integration of sustainable development principles in transportation planning.